Entrepreneurship and market size: The case of young college graduates in Italy - Sabrina Di Addario; Daniela Vuri (Institute for the Study of Labor (IZA), 2010)
We analyze empirically the effects of urban agglomeration on Italian college graduates' work possibilities as entrepreneurs three years after graduation. We find that each 100,000 inhabitant-increase in the size of the individual's province of work reduces the chances of being an entrepreneur by 0.2-0.3 percent. This result holds after controlling for regional fixed effects and is robust to instrumenting urbanization. Province's competition, urban amenities and dis-amenities, cost of labor, earning differentials between employees and self-employed workers, unemployment rates and value added per capita account for 40 percent of the negative urbanization penalty. Our result cannot be explained by the presence of negative large-city differentials in returns to education either. In fact, as long as they succeed in entering the largest markets, young entrepreneurs are able to reap-off the benefits of urbanization externalities: every 100,000-inhabitant increase in the province's population raises entrepreneurs' net monthly income by 0.2-0.3 percent.
urn:nbn:de:101:1-201008118075
Keywords: R12; J24; J21; 330; labor market transitions; urbanization